‘What can we understand from the firms’ accounts about the risks they are exposed to and how they manage them? A comparison is made between firms in five different industries for the year 2008’ - Gregoriou, Ioanna (2009)
The purpose of this paper is to examine the risk disclosures of UK companies. An analysis of fifteen companies belonging to the FTSE 100 has been conducted for the financial year 2008, in order to provide insight into the relationship between the quantity and quality of risk disclosures and specific corporate characteristics such as size and gearing. Risks have been classified under four main headings, these being financial, operational, strategic, and information processing and technology risks. This paper serves another role which is to examine potential differences in risks disclosed by companies belonging to different industries. The industries that are compared are the tobacco, retail, food and beverages, oil and gas and airline industries. This study also deals with an examination of whether highly geared companies disclose some sort of monetary information under the Key Group Risk Factors section, in order to make information regarding the company’s financial situation clear and transparent to the users of Annual Reports.